Repair of omphalocele with extensive liver herniation through a small abdominal wall defect by delayed external silo reduction - Yusuke Shigeta; Takashi Doi; Tokiko Okunobo; Ryosuke Satake; Hiroki Nakamura; Mitsugu Sekimoto (Elsevier, 2021)
An omphalocele containing the entire liver inside the umbilical cord through a small abdominal wall defect is a rare condition. The surgical management of an omphalocele with extensive liver herniation through a small abdominal wall is extremely challenging due to not only a limited abdominal cavity but also a narrowed umbilical ring. Herein, we report a case of omphalocele with extensive liver herniation through a small abdominal wall treated successfully with a delayed external silo reduction technique, by preserving the amniotic membrane.